Analysis of vaccination against SARS-CoV-2 and mortality due to COVID-19 in the Callao region, Peru during the period 2021-2022 - Vasquez-Velasquez, Cinthya (2025)
Objective: To determine the relationship between SARS-CoV-2 vaccination dimensions and COVID-19 death rates in the Callao region. Methods: A cross-sectional study based on the Ministry of Health databases was carried out. A total of 44,867 records from the Callao region were analyzed for the period 2021 to 2022. To assess the association of interest, logistic regression models were constructed, reporting crude odds ratios (cOR) and adjusted odds ratios (aOR). Results: The logistic regression models showed that vaccination had a protective effect against death from COVID-19, with an aOR of 0.19 (p<0.001) after controlling for sex, age, hospitalization, ICU admission, and pandemic wave, compared to the reference group (unvaccinated). Conclusions: Vaccination provides a monotonic protective effect against death from COVID-19 in the Región Callao.